Studi Karakteristik Marshall Pada Aspal Dengan Perbandingan Lateks Pada Lapisan Wearing Course - Tilik, Lina Flaviana (Journal of Applied Civil Engineering and Infrastructure Technology, 2022)
Asphalt concrete is one type of flexible pavement construction pavement. Asphalt concrete mixture consists of coarse aggregate, fine aggregate with asphalt as a binder. The availability of bitumen usually comes from the petroleum refining process, but it is getting thinner day by day, and the availability of crude oil contained in the bowels of the earth is also decreasing. The above problems finally opened the idea of developing polymer-modified asphalt by adding additives or replacing part of the asphalt with polymer materials to achieve the goal of reducing asphalt without compromising quality. Expected to improve performance. One of the materials that can be used is natural elastomer, namely natural rubber in the form of latex or latex rubber. The use of latex as a substitute for asphalt concrete is expected to be a new alternative to improve the performance of road pavements and can be a solution for road pavement structures to withstand heavy vehicle loads and withstand changes in natural conditions, so that construction is expected to last a long time. for a long time. The results of this test obtained the optimum asphalt content of 6.5%. With an optimum asphalt content of 6.5%, the value of VIM: 3.513%, VMA: 15.090% VFA: 74.223, Stability: 1658.032, Flow: 3.531 Marshall Quantient: 469,564. All characteristic values of the AC-WC mixture at 6.5% asphalt content met the 2010 technical specifications.